Dynamic models of beta measurement in the Malaysian banking sector / N. H. Yaakop Yahaya Al-Haj and M. Nurol ain (Faculty of Business and Management ; UiTM Press, 2006)
This paper concentrates on the estimation of beta in the Malaysian banking sector using three different dynamic econometric techniques, specifically Kalman Filter, GARCH(1, 1) and Schwert and Seguin (1990). These techniques consider the behavior of the banks' betas in respect to the country's composite index (Kuala Lumpur Composite Index), as the proxy to the market portfolio. Potentially, these techniques provide better estimates due to the time varying nature of beta. Evidence is provided to support of which is the better technique to explain best the behavior of Malaysian banks' betas behavior. Another potential implication to note is to consider period and size oriented study in respect of beta estimations since stationarity of betas has important implications for the measures of capital asset pricing and performance, efficient market hypothesis and, more importantly in the forecasting of stock returns.